Life Time Risk of Maternal Death in districts of Maharashtra State, India: Mathematical Estimation Using Proxy Indicators - Doke, Prakash Prabhakarrao (Indian Journal of Community Health, 2017)
Background: Maternal Mortality Ratio, Maternal Mortality Rate, Life Time Risk of Maternal Death are used to describe maternal mortality. First is most commonly quoted indicator. The Life Time Risk is most comprehensive. Three simple methods of calculations of Life Time Risk are documented. The calculations require Maternal Mortality Ratio and Total Fertility Rate; Maternal Mortality Rate and Reproductive Age Group Span. Reliable district wise data of these indicators is unavailable. Aim & Objectives: To calculate district wise life time risk of maternal deaths. Material & Methods: The proportion of non-institutional deliveries was used as proxy for Maternal Mortality Ratio and the proportion of couples not using any family planning method was used as proxy for the Total Fertility Rate. The correlation and regression equation between estimated Life Time Risk using standard method and using proxies was calculated. District wise Life Time Risk for Maharashtra state was calculated using the regression equation. Results: Good correlation was observed using proxies (r=0.97) and regression equation was: y=0.09+1.71x. For Maharashtra state the estimated of Life Time Risk was found to be 0.14% which exactly matched the estimate using conventional method. Conclusion: Using proxies reliable estimates of Life Time Risk for districts can be calculated.